Synthesis Of Montelukast Sodium Via An Ester Intermediate; Syntheis And Characterization Of Impurities - CHANDRA SEKHAR BVVN; RAMESH KUMAR N; KALYAN CHAKRAVARTHY A; MUKKANTI K (International Journal of Pharma and Bio Sciences, 2011)
The objective is to study novel synthetic approaches for the synthesis of leukotriene receptor antagonist, Montelukast sodium. The current study also deals with synthesis and characterization of impurities of Montelukast sodium.